2020
DOI: 10.3390/urbansci5010005
|View full text |Cite
|
Sign up to set email alerts
|

Community Perceptions and Knowledge of Modern Stormwater Treatment Assets

Abstract: Modern stormwater treatment assets are a form of water sensitive urban design (WSUD) features that aim to reduce the volumes of sediment, nutrients and gross pollutants discharged into receiving waterways. Local governments and developers in urban areas are installing and maintaining a large number of stormwater treatment assets, with the aim of improving urban runoff water quality. Many of these assets take up significant urban space and are highly visible and as a result, community acceptance is essential fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Common themes were also found among survey respondents' perceived drawbacks of SUDS. Concerns about litter, pests, and maintenance tempered the generally positive impressions of the green space in the studies by Williams et al [67] and Zamanifard et al [69]. The perception of health and safety risks was also highlighted by Jarvie et al [68] and Bastien et al [70].…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…Common themes were also found among survey respondents' perceived drawbacks of SUDS. Concerns about litter, pests, and maintenance tempered the generally positive impressions of the green space in the studies by Williams et al [67] and Zamanifard et al [69]. The perception of health and safety risks was also highlighted by Jarvie et al [68] and Bastien et al [70].…”
Section: Literature Reviewmentioning
confidence: 98%
“…Jarvie et al [68] addressed the issue of willingness to pay for ponds, finding that the economic benefits of ponds outweighed the expense of maintaining them but that the benefits were often not well communicated. Zamanifard et al [69] found that the public was generally positive about the bioretention basins they were presented with in their area, but that awareness of their function was low to the point that fewer than half of the respondents could identify their purpose. Lack of awareness lead to the de-prioritization of maintenance in the long term.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Public perceptions of SUDS and other stormwater management measures have been extensively studied. Survey respondents in the UK and US have been found to appreciate the green space and beauty of well-maintained stormwater ponds [25][26][27] but may not necessarily be aware of or prioritize their hydrologic functions [25,27,28]. In the context of river restoration, Nassauer et al [29] found that expectations of aesthetics may not always be compatible with hydrologic performance.…”
Section: Suds As a Climate Adaptation Measure And Challengesmentioning
confidence: 99%